PENGARUH KOMPENSASI FINANSIAL, KOMPENSASI NON FINANSIAL DAN KOMITMEN ORGANISASI TERHADAP PRESTASI KERJA KARYAWAN - NARAY, PATRIK F (Universitas Sam Ratulangi, 2013)
Employees of the companies being sued are professionals in all job duties that all work is completed in accordance with the standard specified. To that end, the compensation policy are expected to affect employees ' work performance. The purpose of this research is untukmengetahui the influence of financial compensation, financial and non financial compensation organizational commitment to employee achievements of PT. Arcende. The population in this study are all employees in the company of PT. Arcende. The sampling technique used was the Census sampling technique, i.e. the entire population being included as sample or respondents. In this study population the target population is referred to as many as 47 people. The number of samples in this research as much as 47 respondents used analysis method is a method of multiple regression analysis. Research results by using multiple regression analysis showed that partially and simultaneous turns out membuktika research results that financial compensation, compensation of non-financial, and organizational commitment affect the accomplishment of work of employees of PT. Arcende. Multiple regression testing results showed that all the variables are independent (financial compensation, non financial compensation and organizational commitment) positive effect on employee accomplishments PT. Arcende. The granting of compensation for employees must comply with the regulations in force, as well as standard and always pay attention to the minimum cost of living. Without prejudice to the principle of fair and reasonable, so that the compensation provided to each employee according to the prestai it works. Â Keywords: financial, compensation, organizational commitment and job performance